EU Economic Governance Reform: Are We at A Turning Point? - Daniel Dăianu (Romanian Journal of European Affairs, 2011)
The sovereign debt crisis is creating enormous anguish in the EMU. Not surprisingly, emergency measures continue to be used at a time when a sort of economic recovery seems to be underway. Against this background the European Council summit of last October considered a Task Force report with a telling name: “Strengthening economic governance in the EU”. This document is to be examined in conjunction with the governance reform proposals issued by the European Commission at the end of September and related documents. For the depth of this financial crisis and the “Great Recession” have forced EU governments and EU institutions to take a hard look at the governance structure of the Union. But it would be wrong to say that this demarche is an attempt to explore a terra incognita. From the very beginning of the European Monetary Union (EMU) there was some discomfort with its institutional underpinnings and there were misgivings regarding its optimality as a currency area. This explains why a train of thought underlines a political rationale, too, for the creation of the EMU. Likewise, criticism regarding the way regulation and supervision have been established in the Union is not of recent vintage. And insufficiencies of the Stability and Growth Pact (SGP), with almost all member states flouting its rules at various points in time, have been repeatedly pointed out. This said, however, the flaws of financial intermediation have been less tackled by policy-makers and central bankers for reasons which, partially, are to be found in a paradigm which has dominated economic thinking in recent decades. This paper focuses on roots of the huge strain in the EU (EMU) and main policy issues ensuing from the current crisis. It also looks at the stake NMSs have in a reformed EU economic governance structure. The challenges for EU economic governance reform are to be seen from a broad perspective: the crisis of the financial intermediation system; the sub-optimal character of the EMU; institutional and policy underpinnings of the EU (EMU) including the regulation and supervision of financial markets; the capacity of the EU to deal with global imbalances, etc. Nota bene: there is a “political reality” which constrains decisions in the EU; the latter is not a federal state and what appears to be rational when defined strictly economically may clash with implications of the political configuration of the Union.